Effect of foliar application of nano-nutrients solution on growth and biochemical attributes of tomato (Solanum lycopersicum) under drought stress - Mubashir, Areesha; Nisa, Zaib-un-; Shah, Anis Ali; Kiran, Munazza; Hussain, Iqtidar; Ali, Naila; Zhang, Lixin; Madnay, Mahmoud M. Y.; Alsiary, Waleed A.; Korany, Shereen Magdy; Ashraf, Muhammad; Al-Mur, Bandar A.; et al. (Frontiers in Plant Science, 2023)
Introduction Drought stress has drastically hampered the growth and yield of many crops. Therefore, environmentally safe agricultural techniques are needed to mitigate drought stress impact. To this end, foliar spray of nano-nutrients solution to (NNS) alleviate harmful aspects of drought stress. Methods In a completely randomized design (CRD) experiment, seedlings were transplanted into pots at 2-3 leaf stage, each filled with loam-compost- organic manure soil (3:1:1). Plants were divided into two groups. (a) control group (b) applied stress group. Plants at vegetative stage were treated with 100% FC for control group and 60% FC for drought group, and these levels were maintained until harvesting. Three treatments of NNS with four levels i.e., 0%, 1%, 3% and 5% were given to all the pots after two weeks of drought stress treatment with a gap of 5 days at vegetative stage. Results and discussion Application of 1% of nano-nutrient solution displayed an improvement in shoot length, shoot fresh and dry weight, number of leaves and flowers. Leaf chlorophylls and carotenoids and total phenolics contents were found maximum while minimum electrolyte leakage was observed at 3% application compared to control. Further, 1% application of NNS increased the Leaf RWC%, total soluble sugars, flavonoids contents. 5% NNS application exhibited higher total free amino acids with minimum lipid peroxidation rate in leaves of tomato under drought. Antioxidant enzyme activities increased in a concentration dependent manner as gradual increase was observed at 1%, 3% and 5%, respectively. Overall, this study introduced a new insights on using nano-nutrient solutions to maintain natural resources and ensure agricultural sustainability